Maintenance Treatment of Gastroesophageal Reflux Disease: An Evaluation of Continuous and On-Demand Therapy with Rabeprazole 20 mg - David G Morgan; Michael FJ O’Mahony; William F O’Mahony; Jean Roy; Fernando Camacho; Julie Dinniwell; GLA Horbay; Farah A Husein-Bhabha; for the RAB-GRD-3002 Study Group (Canadian Journal of Gastroenterology)
OBJECTIVE: To evaluate continuous therapy (COT) and on-demand therapy (ODT) with rabeprazole 20 mg for maintenance in uninvestigated gastroesophageal reflux disease (GERD).